THE SECURITY FEATURES ON THE WEBSITE MAKING 50.000 RUPIAH PAPER MONEY WITH FRONTPAGE 2000 APPLICATIONS - Ahmad Kurniawan; Sunarto Usna, Drs, MMSI (Jurnal Sistem Informasi, 2003)
In the design of this website is the author deliberately chose a page that consists of the frame on the basis that if there are visitors who come to seek information by simply pressing tombnol link that has been available in the frame. Authors are aware that a variety of educational backgrounds - sort of visitors who will open this website so that all existing safety features on this website appears with two views.